THE INFLUENCE OF LIFESTYLE ON PURCHASING DECISIONS FOR SKINTIFIC SKIN CARE - Khairun Nisa; T. Edyansyah; Nurainun; Halida Bahri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Lifestyle is a pattern or way individuals express, ideals, habits, opinions, with their environment in a unique way, which symbolizes the status and role of individuals for their environment. The development of the skin care industry in recent years has increased significantly. The demand for skin care products is increasing in Aceh, especially among students of the Faculty of Economics and Business, Malikussaleh University, one of the popular skin care brands today is skintific. With the existence of a lifestyle, female students' activities to buy skintific skin care because interest and interest are the main factors in the opinion of using skin care for skin care to increase self-confidence. This study aims to determine the relationship between lifestyle dimensions, Activity, Interest and Opinion. The approach used was quantitative by distributing questionnaires to 155 female students at the Faculty of Economics and Business, Malikussaleh University. Primary data collection and analysis were carried out through multiple linear regression using SPSS 25. Which shows that the variables Activity, Interst and Opinion have a positive effect on purchasing decisions.